Nanofiber-enrich activated carbon coin derived from tofu dregs as electrode materials for supercapacitor - Taer, Erman; Apriwandi; Hasanah, Fainida; Taslim, Rika (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2021)
In this study, the activated carbon with enriched nanofiber obtained from free-binder materials. It was conducted tofu dregs carbon nanofiber as electrode material for supercapacitor without the addition of pVdF/PTFE. The chemical impregnation of NaOH, ZnCl2 and H3PO4 at high-temperature pyrolysis in an N2-CO2 environment converted the tofu dregs into carbon coin. Subsequently, the physical properties including, microcrystalline, morphology, element analysis, and electrochemical properties of specific capacitance were investigated. The morphological structure of activated carbon showed high nanofiber density and was decorated by sponge-like pores. In addition, the nanofiber contains oxygen content of 12.70% which can act as self-doping due to the pseudo-capacitance properties. Furthermore, the two-electrode system obtained a specific capacitance of 163 F g-1 in 1 M H2SO4 electrolyte. The results showed that tofu dregs-based activated carbon coins are sustainable and efficient to obtain high-dense nanofiber structure as electrode materials for energy storage applications.